On site manufacturing (OSM) construction through lifting system for a modern high-rise building / Muhammad Fauzan Naim Murad and Mohd Rofdzi Abdullah - Murad, Muhammad Fauzan Naim; Abdullah, Mohd Rofdzi (2019)
In line of high-rise construction there have several issues are state like timeframe of the development, the accident that occur throughout construction and weather that impact material handling from bottom to the highest of the building. This innovation is to enhancements within the construction of high-rise buildings by applying the thought of not sporting a tower crane to transfer materials from the bottom up create the development space safe and forestall accidental staff. this is often within the kind of a mixture of two ideas coming back from upbrella from Netherlands and massive cover from Japan. Moreover, the methodology of this analysis innovation is beginning by the table study, review of sure article from Netherlands and Japan are the most to induce a brand-new technology in high rise construction methodology. This two-technology country have a quickest thanks to develop a brand-new construction methodology. aside from that, the everyday model model of lifting system to be contemplate in new and fashionable methodology of construction the high-rise building particularly in IBS sector.